2020
DOI: 10.1111/jvs.12959
|View full text |Cite
|
Sign up to set email alerts
|

Shade alters savanna grass layer structure and function along a gradient of canopy cover

Abstract: Aim: In savannas, a grass-dominated ground layer is key to ecosystem function via grass-fire feedbacks that maintain open ecosystems. With woody encroachment, tree density increases, thereby decreasing light in the ground layer and potentially altering ecosystem function. We investigated how light availability can filter individual grass species distributions and whether different functional traits are associated with response to a shade gradient in a landscape experiencing woody encroachment. Location: Savann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 65 publications
0
41
0
1
Order By: Relevance
“…Crucially, reduced belowground allocation could result in reduced competitive ability and resprouting capacity relative to both fire and grazing that in turn would increase the likelihood of a species being filtered out of an ecosystem. Indeed, such substantial diminishment of belowground reserves observed here may explain the abrupt exclusion of grasses from the ground layer with increasing tree cover observed in field studies (Charles-Dominique et al, 2018;Pilon et al, 2020;Pinheiro et al, 2016).…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Crucially, reduced belowground allocation could result in reduced competitive ability and resprouting capacity relative to both fire and grazing that in turn would increase the likelihood of a species being filtered out of an ecosystem. Indeed, such substantial diminishment of belowground reserves observed here may explain the abrupt exclusion of grasses from the ground layer with increasing tree cover observed in field studies (Charles-Dominique et al, 2018;Pilon et al, 2020;Pinheiro et al, 2016).…”
Section: Discussionmentioning
confidence: 55%
“…By comparing the growth and biomass allocation of two species of Brachiaria in full sunlight and shaded to 30% light availability, Dias‐Filho (2000) showed that plants had higher specific leaf area and allocated significantly less biomass to root and more to leaf tissue than high‐light plants. While C 4 grass species can persist in low light levels utilizing carbon resources stored in underground structures (Pinheiro et al, 2016; Taylor et al, 2010; Zimmermann et al, 2010), it is only possible for a limited time before the plant must enter a carbon deficit (de Moraes et al, 2016; Pilon et al, 2020; Pinheiro et al, 2016). Crucially, reduced belowground allocation could result in reduced competitive ability and resprouting capacity relative to both fire and grazing that in turn would increase the likelihood of a species being filtered out of an ecosystem.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations